Children Design Their Interfaces for Web Search Engines: A Participatory Approach - Bilal, Dania (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study involved eleven seventh-grade children in designing interfaces for Web search engines that meet their needs. Using a participatory approach, children drew interfaces and articulated their purposes. The layouts of these interfaces varied, but the features/capabilities described in them were similar. These were, keyword searching with instructions; natural language/phrase. . .